Evaluating the Influence of Parasite Management Programs on Growth Performance of Steer Calves in EL Centro 1 – Management Programs Effect on Coccsidiosis: AL-Sammarraie Saadi AG* Zinn Richard A - A., Zinn Richard (The Iraqi Journal of Veterinary Medicine, 2011)
As a part of a protocol ( Z2F10 – Laidlomycin calf - fed Holstein health management ) Coccidiosis was studied in two hundred Holstein steer- calves (114 kg ) to evaluate the effect of management and treatment programs. Early weaned animals were shipped to the University of California Desert Research Center El Centro on the 26th of May 2010. The calves were vaccinated and treated with internal and external anti parasitic also injected with Vital E - AD (5ml SC 100000 vitamin A/ml and 12ml of liquamycin. Steers were balanced by weight and assigned within weight grouping to (40) pens ( 5 steers / pen ). Animals were randomly divided into four equal groups, the 1st was control group and the 2nd, 3rd and 4th groups were treated with Monensin Laidlomycin and Deccox respectively. Freshly lead fecal samples were collected during Summer months 2010 from the pens and a quantitative flotation technique was used. The Results showed that 50% of the control, 40% of the Monensin treated, 10% of the Laidlomycin treated and 70% of the Deccox treated groups were positive for coccidial oocysts. The prevalence rate of coccidia oocysts in the herd was ( 40.25 %).